Protest politics in Germany : movements on the Left and Right since the 1960s - Karapin, Roger (Pennsylvania State Univ. Press, 2007)
Roger Karapin examines protest movements of all shades to understand why they became influential & also why different forms of protest come to be used in different circumstances.